Analysis Of Dribbling Skills Of Extracurricular Soccer Participants In Senior High School Students 17 Gowa - Muhammad Qasash Hasyim; Andi Ridwan; Ishak Bachtiar; Muh. Ikbal Amal (Journal Physical Health Recreation (JPHR), 2023)
This research is a type of descriptive research that uses a "Survey" research plan. This study aims to determine; How are the dribbling skills of football extracurricular participants at SMA Negeri 17 Gowa. The population is all 30 football extracurricular participants at SMA Negeri 17 Gowa. The sample used was a sample population of 30 people. The sampling technique is total sampling. The data analysis technique used is descriptive analysis with percentages. The results showed that students in the "Good" category were 17% (5 students), in the "fair" category were 77% (23 students), in the "poor" category were 6% (2 students), while there were none in the "Very Good" category. and the category “Very Less:. So it can be concluded that the level of ball dribbling skills of football extracurricular participants at SMA Negeri 17 Gowa is in the sufficient category with a percentage of 77%.